GEOECOLOGICAL ASPECTS OF ECONOMIC DEVELOPMENT - Abdullayeva Mohinabonu Xayrullayevna (Scholar Express Journals, 2023)
This article analyzed the main aspects of the impact of global ecology on the economic development of the countries of the world. Currently, the process of environmental endangerment of nature and human life is becoming more complicated and difficult. The modern concept of sustainable development calls for environmental protection and efficient use of natural resources to be solved together with social and economic problems.
Keywords: geoecology; economic development; natural resource; nature